Evidence-based Learning as a Tool of Competency Improvement for the Phlebotomist - Wonglumsom, Wijit; Manochiopinij, Sudarat; Sirisali, Sophon; Vattanaviboon, Phantip; Sirisali, Kulnaree (Kasetsart Journal of Social Sciences, 2011)
Nowadays, clinical laboratory service has an important role in patient care management. A quality test result must be obtained, but this can be affected by many factors. The correct process for specimen acquisition is very necessary and must be done by competent professional personnel. The objective of this study was to improve the competency of blood collection by phlebotomists through evidence-based learning. Evidence-based information gathering from nurses, medical technologists and clinical laboratory assistants was analyzed and synthesized to use as teaching material. Subjects were divided into two groups. The results showed that the trained groups of the "lecture" type and the "evidence-based" type had different levels of improvement, with the more competent group being the evidence-based one. Five out of eight assessed parameters showed significant improvement. The overall score was increased from 49.79 to 73.08 percent In addition, the evidence-based group showed their improved competency by the ability to improve the venipuncture process from 76.59 to 92.31 percent and the time to perform venipuncture per patient was reduced by 43 seconds.